KOMUNIKASI LINGKUNGAN PADA PENGOLAHAN SAMPAH DAUR ULANG DI TEMPAT PEMBUANGAN SAMPAH SUMUR BATU BEKASI - HAMLUDDIN HAMLUDDIN (Interpretasi: Communication & Public Relations, 2021)
Environmental communication on the problem of recycled waste processing in the SumurbatuFinal Disposal Site (TPA) is an important discourse in formulating solutions toenvironmental problems that occur. The research location was determined in the SumurbatuTPA area for several reasons, among others, the location was the center for final wastedisposal for all residents of the capital city of Jakarta and Bekasi City with a population ofaround 13 million. The volume of waste disposal, which reaches 9,000 tons per day fromDKI, and 900 tons per day from Bekasi City residents, has caused environmental pollutionthat has been going on for a long time. Pollution occurs in the air, soil, and water containedtherein. The open dumping system has become a major factor in pollution, and newappropriate technology has been pursued by the Central and Regional Governments in recentyears. Due to the inadequacy of the waste processing system, especially in the Sumur BatuTPA, the Ministry of Environment has crossed out the name of Bekasi City in the list ofAdipura cities because the value obtained is certain to be low because the final wastehandling is not good. Due to this problem, the waste recycling program is implemented byoptimizing the role of communicators to encourage changes in the waste processing systemapproach. Through this program, it is hoped that waste will have been sorted from the sourceto reduce the volume that goes to the final disposal. Using a qualitative approach, the researcher wants to know the implementation of environmental communication in the implementation of the program by focusing on convergence communication, namely the creation of an understanding between all stakeholders in the recycled waste management system.